Risk Factors of Events Stunting in Toddlers Aged 1-5 Years - Eva Yustati; Maya Sartika; Arda Suryadinata (Indonesian Journal of Global Health Research, 2023)
Stunting is one of the nutritional problems faced by the world, especially in poor and developing countries Stunting become a health problem because it is associated with the risk of morbidity and mortality, suboptimal brain development, resulting in delayed motor development and retarded mental growth. Building Village Pakuon is suffering from environmental conditions around the toddler's house stunting. there is still a physical quality of clean water that does not meet health requirements. There are still mothers of toddlers aged 1-5 years who pay little attention to personal hygiene, especially washing hands before and after eating. Objective to analyze the risk factors for events Stunting in toddlers aged 1-5 years in the village Pakuon Building Working Area of ​​UPTD Tanjung Lengkayap Public Health Center, OKU Regency The type of research used was a research design Cross Sectional The population of all mothers aged 1-5 years in Gedung Pakoun Village is 152 toddlers, the sample in this study is 110 samples. Bivariate analysis shows that mother's knowledge is valuep value 0.000 means that statistically there is a significant relationship between mother's knowledge and events stunting. While the parents' income valuep value 0.000 means that statistically there is a significant relationship between parental income and incidence stunting. Physical quality of water valuesp value 0,000. This means that there is a significant relationship between the physical quality of water and the occurrence stunting. Then the value of hand washing habitsp value 0,002. meaning that statistically there is a significant relationship between the habit of washing hands with the incident stunting. There is a significant relationship between mother's knowledge, parents' income, physical quality of water and hand washing habits stunting in toddlers 1-5 years.